Form accuracy and cutting forces in turning of X5CrNi18-10 shafts: Investigating the influence of thrust force on roundness deviation under low-feed machining conditions - El Majdoub, Wafae; Hamza Daud, Muhammad; Sztankovics, István (Journal of Production Engineering, 2025)
In nowadays manufacturing, it is important to respect the tolerances and meet the standards of accuracy. So, this paper tends to investigate the effects of cutting parameters on thrust force and shape deviations during the longitudinal turning of X5CrNi18-10 austenitic stainless steel under wet conditions. The research is done based on experimental setup used to measure cutting forces. There are many parameters representing the shape errors, but the roundness was the focus of this paper. Eight setups were examined by varying the cutting parameters, such as cutting speed, feed and depth of cut in two levels. Four elements of roundness parameters were selected to be analysed (RONt, DFTC, slope and Ecc). Based on experimental and theoretical methods, the graphs were generated with the aim of observing the influence of cutting conditions on the surface quality while using hard machined material and then drawing conclusions of the best cutting parameters selection to optimise the turning process. The study emphasises the importance of controlling the tool deflections and material resistance by optimising the settings. The results of this work give a practical approach to enhance precision and surface quality in turning operations.